Whole-genome sequencing reveals a recurrent missense mutation in the Connexin 46 (GJA3) gene causing autosomal-dominant lamellar cataract. (October 2018) - Berry, Vanita; Ionides, Alexander; Pontikos, Nikolas; Moghul, Ismail; Moore, Anthony; Cheetham, Michael; Michaelides, Michel
Abstract Purpose Congenital cataract, opacification of the ocular lens, is clinically and genetically a heterogeneous childhood disease. In this study we aimed to identify the underlying genetic cause of isolated autosomal-dominant lamellar cataract in a multi-generation English family. Methods Whole-genome sequencing (WGS) was undertaken in two affected subjects and one unaffected individual. Segregation analysis was performed and a known cataract-causing mutation was identified. Segregation was further validated by sanger sequencing in the entire pedigree. Results A heterozygous mutation c.7 G > T; p.D3Y was identified in an NH2 -terminal region of the gap junction protein GJA3 and found to co-segregate with disease. Conclusion We have identified a recurrent mutation in GJA3 in a large British pedigree causing the novel phenotype of autosomal-dominant congenital lamellar cataract. Previously, p.D3Y was found in a Hispanic family causing pulverulent cataract. WGS proved an efficient method to find the underlying molecular cause in this large family, which could not be mapped due to uninformative markers.